Sales Promotion Brand Barenbliss Melalui TikTok - Koeswanto, Angelica; Putranto, Teguh Dwi; Budiman, Devani Hizkia; ,, Enjelita; Equeena, Karmelia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2023)
The development of internet-based technology has encouraged many companies to use social media as a marketing tool. In Indonesia, TikTok is one of the most popular social media platforms and is widely used by the public for creative activities, including selling products or uploading everyday content. Sales promotion is one of the ways used by sellers to make consumers interested in buying the product being promoted. One of the important elements in modern marketing is sales promotion, which includes strategies to increase product or service sales by offering attractive incentives to potential buyers. Sales promotion works simultaneously with other elements in the marketing mix such as product, price and distribution (place). This study aims to determine the sales promotion of the Barenbliss brand on the TikTok application. This study used a qualitative approach using content analysis methods. The research data collected is the result of observations and documents (TikTok videos). The main finding of this study is that 11 sales promotion videos were found on the Barenbliss account on the Tiktok application from early to mid 2023. Based on the results of research observations, it was concluded that the type of sales promotion that customers are most interested in is discounts or discounts, as well as giving gifts in the form of products Barenbliss through participating in a challenge. Keywords: Sales Promotion, Barenbliss, Content Analysis, TikTok.